Leiomyoma of the renal capsule: case report and literature review. Issue 1 (February 2018) - Filianoti, Alessio; Paganelli, Aurelio; Bassi, PierFrancesco; Simone, Giuseppe; Ranieri, Antonio
Introduction: Mesenchymal tumors are an exceptional finding in the urinary tract and renal leiomyoma is even more rare. They are usually discovered incidentally during ultrasonography examinations or autopsy. Sometimes they are clinically symptomatic with hematuria, flank pain, or palpable mass. Till today, it is still difficult to make a diagnosis of leiomyoma using the radiological examinations. Although conventional imaging has a high sensitivity and specificity in the detection of both retroperitoneal and renal masses, the diagnosis is based on histological examination, due to the poor discrimination accuracy between different retroperitoneal tumors. Case description: We report a case of renal leiomyoma in a 47-year-old woman, who incidentally discovered a retroperitoneal mass with an abdominal ultrasound scheduled for a conventional follow-up schedule of a mammary neoplasm. Partial nephrectomy was carried out with an open flank surgical approach and the diagnosis was "leiomyoma of the renal capsule". Four years after surgery, the patient is disease-free. Conclusions: Renal leiomyomas are rare, benign, nonmetastasizing tumors with a good prognosis after surgical treatment. At present, the differential diagnosis is still possible by histopathological examination.